PERSEPSI DAN PARTISIPASI PETANI PADI TERHADAP PENDIDIKAN ANAK DI KENAGARIAN KOTO HILALANG KECAMATAN KUBUNG KABUPATEN SOLOK - Husni, Laili; Ansofino, Ansofino; Zulfa, Zulfa (Pendidikan Sejarah, 2013)
ABSTRACTIndividuals and communities have different perceptions of the education, as well as in rice farming communities in general have a low educational background. In order to achieve a good education then this is a very important thing to know, because look at the extent to which the views or perceptions of rice farmers and community participation towards their childs education. The purpose of this study was to determine the socio-economic situation and describe Rice Farmers Society Perception and Participation Rice Farmers Against Children Education in Kenagarian Koto Hilalang lemur Solok district. The research conducted by using qualitative research methods, the data obtained by observation and interviews, while data analysis is done in 3 ways, namely, reduction (filtering the data as required), tabulation (grouping the answers into the form of a table) and Conclusion (writing the analysis into form of research). The results that First : Public Perception Rice Farmers Against Children Education in Koto Kenagarian Hilalang lemur Solok district , based on the level of public knowledge of the childs education is very good . This is evident from the level of knowledge of rice farming communities to education , the percentage reached 88 % of respondents . Second : Rice Farmers Society Participation in Koto Kenagarian Hilalang seen from the high sense of responsibility to contribute to society in their childrens education , both moral and material support . Such as rice farming community involvement with the school reached 95.2 % , taking the time to learn to control the development of the child reaches 76 % . And providing motivation or support to a child to school is 92 % . Third : Economic Social Life Masyarakaat Rice Farmers in Koto Kenagarian Hilalang lemur Solok district , seen against the backdrop of life in the economy generally they have a medium level down economy . This has always been an obstacle for farmers to continue their education . As seen from the income of the farmers are quite low , which is the average income of rice farmers in one harvest 4,200,000 ( Four Million Two Hundred Thousand) . In general, rice farmers trying to meet with their childrens school expenses for other businesses such as farming , animal husbandry and trad.Â Keywords: Perceptions, Participation, farming, Children Education, Society, economic.